Wychowanie szczęśliwego człowieka podstawowym celem rodziców - Piecuch, Ewelina (Karkonoska Państwowa Szkoła Wyższa, 2012)
There are numerous definitions of education. They are dependent on the concept of who human beings are and what their place in the world is as well as on the conditions of their existence, on what the communities expect of their members, and on what the society expects of an individual. The educational act carried out as part of the process of education can be defined as the actions aimed at altering the behavior of an individual at a particular point in time and in a particular situation. Within the family, bringing up a happy child is the purpose of all educational acts.Contemporary studies on childhood suggest that a happy childhood constitutes a stable foundation allowing for a positive functioning in society. It also increases the chances of adults to maintain the balance in which they were brought up.
Keywords: rodzina; dzieci; rozwój; szczęście; edukacja